2012
DOI: 10.1039/c2dt31159c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring copper(i)-based dye-sensitized solar cells: a complementary experimental and TD-DFT investigation

Abstract: The structures and properties of the homoleptic copper(I) complexes [Cu(1)(2)][PF(6)] and [Cu(2)(2)][PF(6)] (1 = 6,6'-dimethyl-2,2'-bipyridine, 2 = 6,6'-bis{2-[4-(N,N'-diphenylamino)phenyl]ethenyl}-2,2'-bipyridine) are compared, and a strategy of ligand exchange in solution has been used to prepare eight TiO(2) surface-bound heteroleptic complexes incorporating ligands with bpy metal-binding domains and carboxylate or phosphonate anchoring groups. The presence of the extended π-system in 2 significantly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 46 publications
7
80
0
Order By: Relevance
“…Attempts to prepare [Cu(6dmbpy)(dppe)]PF 6 by using a procedure similar to that described for 2⋅PF 6 gave red solid of [Cu(6dmbpy) 2 ]PF 6 . 48,49 We found that the colors of the dfppe complexes, 3⋅PF 6 , 4⋅PF 6 , 5⋅PF 6 , 6⋅PF 6 , and 7⋅PF 6 in the solid state are much lighter than those of dppe complexes, 1⋅PF 6 and 2⋅PF 6 ( Fig. 1), and the dfppe complexes exhibit more intense photoluminescence than the dppe complexes under the UV light excitation.…”
Section: Resultsmentioning
confidence: 94%
“…Attempts to prepare [Cu(6dmbpy)(dppe)]PF 6 by using a procedure similar to that described for 2⋅PF 6 gave red solid of [Cu(6dmbpy) 2 ]PF 6 . 48,49 We found that the colors of the dfppe complexes, 3⋅PF 6 , 4⋅PF 6 , 5⋅PF 6 , 6⋅PF 6 , and 7⋅PF 6 in the solid state are much lighter than those of dppe complexes, 1⋅PF 6 and 2⋅PF 6 ( Fig. 1), and the dfppe complexes exhibit more intense photoluminescence than the dppe complexes under the UV light excitation.…”
Section: Resultsmentioning
confidence: 94%
“…All DSCs show an aging effect aer one day with enhanced opencircuit voltage (V OC ), short-circuit current density (J SC ) and efficiency (h). This phenomenon is common for n-type DSCs containing bis(diimine)copper(I) dyes with I À /I 3 À electrolyte; 8,15,16,22 it is also observed for some ruthenium(II) dyes and is attributed to reorganization of the initially aggregated dye molecules on the semiconductor surface. [29][30][31] With bpy as the ancillary ligand, the DSCs perform very poorly, while those with 6-Mebpy or 6,6 0 -Me 2 bpy reach efficiencies relative to N719 of z10% and z13% immediately and one day, respectively, aer sealing the cells.…”
Section: Model Dyes With Anchoring Ligandmentioning
confidence: 86%
“…enhancement of performance with time) [5,25,28] and we routinely assess how the performance of a dye changes over days or weeks after fabricating the DSC.…”
Section: Synthesis and Characterization Of [Cu(2) 2 ][Pf 6 ]mentioning
confidence: 99%